Applied statistics for practitioners and researchers - Büsch, D.; Granacher, U. (Routledge handbook of talent identification and development in sport, 2017)
Talent identification has historically occurred on the basis of practitioner (e.g., coaches) experience-based decision-making. However, statistics can be utilized to support practitioner and researcher decision-making. The main question determining whether statistics are utilized though is: Can they add extra value without an extra work burden? With these needs in mind, applied statistic methods should always provide practically relevant and meaningful guiding evidence and answers. With the aim to promote adoption of statistical approaches as part of evidence-based practice in talent identification and development, this chapter highlights how statistics can potentially support talent identification and development decision-making (Abbott & Collins, 2002;Meylan & Cronin, 2014; Thomas, Nelson, & Silvermann, 2015). The chapter focuses on the appropriate application, understanding and interpretation of statistical methods in the field. Throughout, examples from coaches` daily work are utilized.